2004
DOI: 10.1179/026708404225016346
|View full text |Cite
|
Sign up to set email alerts
|

Sealing of Thermally Sprayed Coatings

Abstract: The use of coatings in fluidised bed boilers is increasing owing to the harsh conditions that modern boilers meet. High temperatures, combined with inhomogeneous, high chlorine and alkali containing fuels such as biomass, cause severe material wastage to metallic parts in boilers. Thermally sprayed coatings have been reported to provide protection to boiler tubes. However, thermally sprayed coatings have encountered serious problems, such as corrosion on the substrate material owing to voids and oxides in lame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…They showed that in order to reduce the number of pores and the unevenness of surface morphology, low fusing speed and homogeneous heating were preferable. Surface melting of thermally sprayed metallic coating was examined by Oksa et al [3]. They showed that laser melted coatings had superior corrosion resistance in short term tests.…”
Section: Mathematical Modeling Of Liquid Layer Formationmentioning
confidence: 99%
“…They showed that in order to reduce the number of pores and the unevenness of surface morphology, low fusing speed and homogeneous heating were preferable. Surface melting of thermally sprayed metallic coating was examined by Oksa et al [3]. They showed that laser melted coatings had superior corrosion resistance in short term tests.…”
Section: Mathematical Modeling Of Liquid Layer Formationmentioning
confidence: 99%
“…They showed that the laser re-melting resulted in a full homogenization of the sprayed structure. Laser heating of HVOF coating and thermally sealing of the coating surface were investigated by Oksa et al (2004). They showed that the thermal sealing provided good corrosion resistance of the surface in short-term tests.…”
Section: Introductionmentioning
confidence: 99%
“…One approach towards this end is to use the HVOF process. A cheaper option that is also more easily adaptable to on‐site coating is arc spraying, although it will result in a higher porosity level (<5%) 12–14.…”
Section: Introductionmentioning
confidence: 99%